Seasonal changes in the viability and abundance of bacterial cells in the snowpack ecosystem of a High Arctic ice cap - Archana Dayal; Andrew Hodson; Marie Šabacká; Alan Smalley (Arctic, Antarctic, and Alpine Research)
Microbes play an essential role in nutrient turnover within Arctic environments, and their contribution to biogeochemical cycles can depend on several factors, including but not limited to cell viability. In this study, we employed the SYBR-PI dual cell stain to epifluorescence microscopy to enumerate proportions of potentially viable and non-viable bacterial cell populations within a melting snowpack on an ice cap, Foxfonna in Svalbard. Non-viable cells dominated on Foxfonna (2.5 ± 0.36 × 107 cells m−2) during the June to early July period, when biological production was usually at its peak. Furthermore, non-viable cells also dominated the total cell abundance within superimposed ice (223 ± 242 cells mL−1) and glacial ice (695 ± 717 cells mL−1) beneath the snow. We propose that the rapid, early loss of cell viability was caused by a number of abiotic and biotic factors. Hence, necromass (dead cell residue) contributed to the export of organic matter to downstream ecosystems.